Analisis kinerja simpang empat Jl. Andi Tonro – Jl. Pacalaya – Jl. Abdul Rasyid Dg. Lurang - Sufiati Bestari; Meti; Geraldo Fevriano Baso (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2024)
In Gowa Regency, near the border of Makassar City, there is an intersection of Jl. Andi Tonro - Jl. Pacalaya - Jl. Abdul Rasyid Dg. Lurang. The major road, Jl. Andi Tonro, is a 2/1 road, channeling traffic from Maros district towards Makassar. The minor roads, Jl. Pacalaya and Jl. Abdul Rasyid Dg. Lurang, only 4.5m wide, road type 2/2 TT respectively. The light-controlled, unsignalized intersection is heavily traveled by motorcycles Motorcyclists from the minor roads often scramble for road space on the major roads, creating extra conflicts at the intersection. The proportion of motorcycles to the total traffic flow of the entire intersection is 0.815. This study aims to determine the degree of saturation value that describes the performance of the studied intersection. The analysis of peak intersection traffic flow, intersection capacity, and degree of saturation values refers to the 2014 Indonesian Road Capacity Guidelines. Even though it is on the border of the city, the traffic behavior through this intersection still shows the characteristics of urban traffic, namely weekly periodic repetitive traffic flow patterns. Therefore, traffic surveys were conducted on Monday, Wednesday representing the normal weekday population: Monday through Thursday and the Saturday survey represents weekend days. Traffic flows entering the intersection site from the three arms were videoed with cameras. Each arm was captured with one camera. Traffic data from each arm per direction of movement per vehicle type was enumerated from the video recordings. The results of data processing were analyzed and obtained the afternoon peak traffic flow represented by weekday traffic. Degree of saturation (Dj) = 0.64. Traffic flow is not saturated. Clutter comes from motorcycles that dominate the traffic flow with a proportion of 0.815 and contra flow violations. Actions to reduce chaos, namely adding signs prohibiting contra flow on Andi Tonro Street. Installation of CCTV cameras that highlight on all four arms. Accompanied by the implementation of Electronic Traffic Law Enforcement in Gowa Regency so that motorcyclists will be forced to be disciplined.